EKSPLORASI PENDAYAGUNAAN LITERASI BERBASIS DIGITAL BAGI SISWA SEKOLAH MENENGAH - Nudiyalista Khusna; Hidayatul Ulum; Ilmia Turrofiah; Musyarrafah S; ‘Ulyatul Nur Kholishoh; Martutik Martutik; Nudiyalista Khusna; Hidayatul Ulum; Ilmia Turrofiah; Musyarrafah S; ‘Ulyatul Nur Kholishoh (Universitas Negeri Malang, 2024)
This study aims to describe the literacy program, scheme and target of the literacy development strategy implementation. This research method is qualitative, case study approach. The results of the research are in the form of a literacy activity development plan formed in the form of utilizing the school literacy website. On the implementation scheme, which consists of three stages, namely planning, implementation and evaluation. The main target of this activity is digital-based literacy materials in the form of literary reviews, short stories, school newsletters, poetry, and school service advertisements.